MOTIVASI DAN MINAT MASYARAKAT DALAM BEROLAHRAGA SEPEDA DI KOTA SEMARANG - Sandi Akbar Romadhon; Tri Rustiadi (Universitas Negeri Semarang, 2016)
The purpose of this study was to to determine the motivation and interest of the community exercise bike in the city of Semarang. The population in this study werepeople who exercise bike in the city of Semarang. The sample in this study were 62 people who went through the exercise bike, especially in the car freeday Semarang Simpangfive sampling incidental manner. Sampling technique used is total sampling. Data collection by survey method with questionnaire. Data from the instrument questionnaire prepared by the method of analytical description of the percentage. From the analysis shows that the majority of people in exercise bikes as motivation number 34 people in the category of good, 28 in the category very well, and no one in the category of less good or less, and their interest in a number of 23 people in the category very good , 37 people fall into either category, two people fall into the category of less good, and there is no entry in the category is less. The conclusion that the dominant of the community sample who exercise bike in the city of Semarang dominant fall into either category. These results indicate that both in terms of interest or motivationis in good category.